Characterization of liquid–liquid mass transfer performance in a capillary microreactor system. Issue 3 (10th October 2017) - Li, Guangxiao; Shang, Minjing; Song, Yang; Su, Yuanhai
Abstract : Liquid–liquid mass transfer performance in a capillary microreactor system was studied with an improved experimental method. Proper sampling modes were chosen to eliminate the effect of the sampling zone on the mass transfer characterization in capillary microreactor systems. The overall volumetric mass transfer coefficients in the T‐micromixer and the capillary microreactor system were found to smoothly increase and then significantly increase with increasing the Reynolds number of two immiscible liquid phases. Other factors such as the inlet mode and inner diameter of T‐micromixer, the capillary length, and the volumetric flux ratio of the aqueous phase to the organic phase affected the mass transfer performance in the T‐micromixer and the capillary microreactor system. Furthermore, the contribution of the mass transfer in the T‐micromixer zone to the capillary microreactor system was found to be in a range of 34–78% under the involved experimental conditions, which was emphasized in the proposed empirical correlations. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1106–1116, 2018